Draft Genome Sequence of Lactobacillus delbrueckii subsp. bulgaricus CFL1, a Lactic Acid Bacterium Isolated from French Handcrafted Fermented Milk - Meneghel, Julie (Genome Announc, 2016)
Lactobacillus delbrueckii subsp. bulgaricus (L. bulgaricus) is a lactic acid bacterium widely used for the production of yogurt and cheeses. Here, we report the genome sequence of L. bulgaricus CFL1 to improve our knowledge on its stress-induced damages following production and end-use processes.